1997
DOI: 10.1016/s0022-5223(97)70259-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of truncus arteriosus repaired in infancy: A twenty-year experience

Abstract: Ten- to 20-year survival and functional status are excellent among infants undergoing complete repair of truncus arteriosus. Conduit replacement or revision is almost inevitably necessary in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 13 publications
8
88
1
4
Order By: Relevance
“…Patients with TA and del22q11.2 have a higher incidence (10-15%) of discontinuity of the pulmonary arteries Marino et al, 2002] (TA Type A3, according with Van Praagh classification), the ''duct dependent'' pulmonary artery being usually the left one in association with left aortic arch [Calder et al, 1976]. Other specific features associated with del22q11.2 include dysplastic truncal valve (30%) leading to incompetence and/or stenosis [Marino et al, 1998;Rajasinghe et al, 1997], interrupted aortic arch (10-20%) [Sano et al, 1990], and coronary artery abnormalities (18%) [de la Cruz et al, 1990].…”
Section: Truncus Arteriosusmentioning
confidence: 99%
“…Patients with TA and del22q11.2 have a higher incidence (10-15%) of discontinuity of the pulmonary arteries Marino et al, 2002] (TA Type A3, according with Van Praagh classification), the ''duct dependent'' pulmonary artery being usually the left one in association with left aortic arch [Calder et al, 1976]. Other specific features associated with del22q11.2 include dysplastic truncal valve (30%) leading to incompetence and/or stenosis [Marino et al, 1998;Rajasinghe et al, 1997], interrupted aortic arch (10-20%) [Sano et al, 1990], and coronary artery abnormalities (18%) [de la Cruz et al, 1990].…”
Section: Truncus Arteriosusmentioning
confidence: 99%
“…Among hospital survivors, Rajasinghe and colleagues 130 reported an actuarial survival rate of 83% at 15-year follow-up. Virtually all the patients had reoperation by 10 to 12 years, however, with a median time to reoperation of 5.1 years.…”
Section: Following Up the Postoperative Patientmentioning
confidence: 99%
“…134 Otherwise, most reintervention is surgical. 135 Adult patients with good surgical results and no complications often have minimal symptoms, 130 and some can be active. Successful pregnancy has been reported, although it is discouraged given the high incidence of chromosomal 22q11 deletions in this patient population.…”
Section: Bashorementioning
confidence: 99%
“…Conduit replacement is eventually necessary in all cases because of homograft valvular stenosis due to shrinkage, distal anastomosis stenosis, conduit calcification, proximal hood aneurysm and somatic outgrowth [11]. Rajasinghe et al [12] and Tlaskal et al [13] in their studies of long-term follow-up of PTA after surgical correction reported a similar high incidence of conduit reoperations. In PTA type A1 and A2, Barbero-Marcial et al [14] and Nemoto et al [15] have described alternative techniques of right ventricle to pulmonary artery continuity established by direct anastomosis.…”
Section: Discussionmentioning
confidence: 99%